CP $$ \mathcal{CP} $$ -sensitive simplified template cross-sections for t t ¯ H $$ t\overline{t}H $$ - Henning Bahl; Alberto Carnelli; Frédéric Déliot; Elina Fuchs; Anastasia Kotsokechagia; Tanguy Lucas Marsault; Marco Menen; Laurent Schoeffel; Matthias Saimpert (Journal of High Energy Physics)
Abstract The CP $$ \mathcal{CP} $$ structure of the Higgs boson is a fundamental property which has not yet been constrained with high precision. CP $$ \mathcal{CP} $$ violation in the Yukawa coupling between the Higgs boson and top quark pair can be probed directly at the Large Hadron Collider by measuring top-quark-associated Higgs production. Multivariate analysis techniques commonly developed so far by the experiments are designed for a specific signal model and, therefore, complicate reinterpretations and statistical combinations. With this motivation in mind, we propose a CP $$ \mathcal{CP} $$ -sensitive extension of the simplified template cross-section (STXS) framework. Considering multiple Higgs decay channels, we perform an in-depth comparison of CP $$ \mathcal{CP} $$ -sensitive observables and combinations thereof. Our resulting proposal is to extend the existing binning in the transverse momentum of the Higgs boson p T,H by either the pseudorapidity difference of the two top-quarks ∆ η t t ¯ $$ Δ η_{t\overline{t}} $$ , or a variable that is based on the top quark momenta, namely b 2 or the Collins-Soper angle |cosθ ∗|. We demonstrate that this variable selection provides close to optimal sensitivity to the CP $$ \mathcal{CP} $$ mixture in the top Yukawa coupling for an integrated luminosity of 300 fb−1, by comparing it to the results of a multivariate analysis. Our results also suggest a benefit of the two-dimensional STXS extension at 3000 fb−1.